PERANAN MEDIA BATANG CUISENAIRE DALAM MENINGKATKAN KEMAMPUAN PENGURANGAN BILANGAN BAGI ANAK DOWN SYNDROM - Vivi - Wahyuni (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was motivated by the apparent problems in the field is a Down Syndrome child in SLB State DV C1 Ampek Angkek Agam district who have difficulty in performing arithmetic operations reduced numbers. It is seen from the child's ability to start work on the problems in the operation count reduction of numbers, children have difficulty in working the given problem and the children have not been able to answer correctly. This study aims to improve the operation count reduction in numbers of children with Down Syndrome DV C1 media Cuisenaire rods. Single Subject Research Methodology The research design research design with A-B. Where the baseline condition (A) the ability of children's early numbers daalam reduction before treatment is given. While the intervention condition (B) a condition in which the child is given treatment by the media cuisenaire rod. Observation data in the form of Visual Analysis of Graphs.